1991
DOI: 10.5547/issn0195-6574-ej-vol12-no3-7
|View full text |Cite
|
Sign up to set email alerts
|

Is the World Oil Market “One Great Pool”?

Abstract: Is there one, global market for crude oil? This appears to be the assumption made by most petroleum economists, stated succinctly by Adelman in a recent issue of The Energy Journal “The world oil market, like the world ocean, is one great pool” (July 1984, p. 5). Policymakers have often implicitly held the opposite assumption — that the world market is fragmented — as evidenced by the efforts of many importing-country governments to seek special arrangements for “secure supply” from exporters in the 1970s and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 5 publications
4
53
0
4
Order By: Relevance
“…Nevertheless, there is still controversy surrounding the convergence and divergence of the international oil market. Weiner [6] found that oil prices diverged in response to regional supply and demand shocks and local government policies; this research supported the hypothesis of regionalisation across oil markets using correlation and a switching regression analysis.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, there is still controversy surrounding the convergence and divergence of the international oil market. Weiner [6] found that oil prices diverged in response to regional supply and demand shocks and local government policies; this research supported the hypothesis of regionalisation across oil markets using correlation and a switching regression analysis.…”
Section: Introductionmentioning
confidence: 52%
“…Especially, Nigeria is the largest oil producer in Africa where Bonny crude oil is an important import source for American and European refineries. Thus, Bonny crude oil is usually selected as the price representatives in Africa for research on price differentials [32,16,33,6]. Therefore, the WTI, Brent, Dubai, Nigeria and Tapis crude oil prices were selected based on geographic distribution, data availability and the importance of the market; they represent America, Europe, the Middle East, Africa and the Asia Pacific, respectively.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%
“…Introduction Adelman (I984a) argues that the world oil market behaves as "one great pool," where changes in market conditionS in One area qUickly affect other geographic areas. We believe that this view is held by most petroleum economists 1 In a recent paper, Professor Robert Weiner (1991a) argues, to the contrary, that the world's oil markets are "regionalized;' and changes in supply or demand amongst the participants in a limited geographic area do not fully "register" in other geographic markets 2 Weiner claims that his views are consistent with the implicit views of policymakers who advocate national oil stockpiles, distinctions between "secure" and "insecure" 1/ For instance, Hogan (1983, pp. 49-50) notes that, 'The essential international character of an oil stockpile derives from the inherent fungibility of oil in the world oil market.…”
mentioning
confidence: 92%
“…Earlier studies, such as Weiner (1991) adopt correlation analysis and switching regression technique to test whether the oil market is unified or regionalized while Gülen (1997) reexamines Weiner's hypothesis using cointegration analysis. Labys (2000) and Kyrtsou and Labys (2005) employ Chaotic tests of the relation between oil prices and inflation.…”
Section: Methodsmentioning
confidence: 99%
“…The computation of simple correlation coefficients within different sub-periods of a total sample period can be employed to study the dynamics of the linkages between variables separated by space (Weiner, 1991). However, since correlation analysis is static rather than dynamic, it is also important to examine cross-correlations with a lag structure between the variables of interest (Bukenya & Labys, 2005 …”
Section: Dynamic Correlation Analysismentioning
confidence: 99%